Deciphering pharmacokinetics and pharmacodynamics of fosfomycin - Rodríguez-Gascón, A; Canut-Blasco, A (Revista española de quimioterapia, 2019)
Fosfomycin, a low molecular weight and hydrophilic drug with negligible protein binding, is eliminated almost exclusively by glomerular filtration, whose clearance is subject to patient renal function. The volume of distribution approximates to the extracellular body water (about 0.3 L/Kg) in healthy volunteers, but it is increased in critically ill patients with bacterial infections. Fosfomycin presents a high ability to distribute into many tissues, including inflamed tissues and abscess fluids. Based on PK/PD analysis and Monte Carlo simulations, we have evaluated different fosfomycin dosing regimen to optimize the treatment of septic patients due to Enterobacterales and Pseudomonas aeruginosa. As PK/PD targets, we selected %T>MIC > 70% for all pathogens, and AUC24/MIC > 24 and AUC24/MIC > 15 for net stasis of Enterobacterales and P. aeruginosa, respectively. Pharmacokinetic parameters in critically ill patients were obtained from the literature. Several dosing regimens were studied in patients with normal renal function: fosfomycin 2-8 g given every 6-12 hours, infused over 30 minutes- 24 hours. At the susceptibility EUCAST breakpoint for Enterobacterales and Staphylococcus spp. (MIC ≤ 32 mg/L), fosfomycin 4 g/8h or higher infused over 30 minutes achieved a probability of target attainment (PTA) > 90%, based in both %T>MIC and AUC24/MIC. For MIC of 64 mg/L, fosfomycin 6 g/6h in 30-minute infusion and 8 g/ 8h in 30-minute and 6 hours infusions also achieved PTA values higher than 90%. No fosfomycin monotherapy regimen was able to achieve PK/PD targets related to antimicrobial efficacy for P. aeruginosa with MICs of 256-512 mg/L.